Vessel Calcification as a Risk Factor for In-Stent Restenosis in Complex Femoropopliteal Lesions After Zilver PTX Paclitaxel-Coated Stent Placement. (October 2019) - Ichihashi, Shigeo; Shibata, Tsuyoshi; Fujimura, Naoki; Nagatomi, Satoru; Yamamoto, Hiroshi; Kyuragi, Ryoichi; Adachi, Akira; Iwakoshi, Shinichi; Bolstad, Francesco; Saeki, Keigo; Obayashi, Kenji; Kichikawa, Kimihiko
Purpose: To evaluate the effect of vessel calcification on in-stent restenosis (ISR) after drug-coated stent (DCS) placement in the femoropopliteal segment.Materials and Methods: A retrospective multicenter study was undertaken involving 220 consecutive symptomatic patients (mean age 73.1±8.3 years; 175 men) with femoropopliteal lesions in 230 limbs treated with the Zilver PTX DCS and having duplex surveillance after the endovascular procedures. Mean lesion length was 16.4±9.8 cm (range 2–40); there were 104 (45.2%) total occlusions and 68 (29.6%) in-stent restenoses (ISR). Twenty (8.7%) vessels had no runoff. The majority of lesions (148, 64.3%) were calcified according to the peripheral arterial calcium scoring system (PACSS). Primary patency was evaluated by duplex. Lesions were classified as either PACSS 0–2 (none or unilateral wall calcification) or PACSS 3 and 4 (bilateral wall calcification). Multivariate analysis was performed to identify variables associated with ISR; the results are given as the hazard ratio (HR) and 95% confidence interval (CI).Results: The 1-, 2-, and 5-year primary patency and freedom from clinically-driven target lesion revascularization estimates were 75.9%, 63.6%, and 45.0%, and 84.7%, 73.7%, and 54.2%, respectively. Major amputations were performed on 4 limbs during follow-up. In multivariate analysis, vessel calcification (adjusted HR 1.718, 95% CI 1.035 to 2.851, p=0.036) was significantly correlated with the occurrence of ISR, along with lesion length (adjusted HR 1.041, 95% CI 1.013 to 1.070, p=0.003), and cilostazol administration (adjusted HR 0.476, 95% CI 0.259 to 0.876, p=0.017).Conclusion: This study suggested that bilateral vessel wall calcification was an independent risk factor for ISR in complex femoropopliteal lesions after Zilver PTX DCS placement, along with lesion length; cilostazol administration had a protective effect.